Inhibition Effect ofCopper (Ⅱ) Theophylline Nanocomplex on Phosphodiesterase (PDE) Enzyme Activity in Human Serum of Iraqi Patients with Asthma Disease - Zainab Sabri Abbas; Ahmad Hussein Ismail; Hassanain Kamil Al-Bairmani; Ahmed Mahdi Rheima; Ameer Radhi Sultan; Srwa Hashim Mohammed (Nano Biomedicine and Engineering, 2021)
Copper (Ⅱ) theophylline [Cu(THP)2(H2O)4] complex in nanoscale has synthesized by ultrasonic sonication method. This method was used in the development of smaller, dispersed, and unaggregated nanoparticles (NPs). The structure of nanocomplex was described and suggested by the molar conductance, Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible spectroscopy (UV-Vis), solubility, atomic fire absorption, and C.H.N. elemental analysis as octahedral geometry. The size and morphology of nanocomplex measured by transmission electron microscopy (TEM) were 20 nm. The nanocomplex was studied on phosphodiesterase enzyme activity in human serum of Iraqi patient?s asthma disease. The results showed a highly significant (p < 0.01) increase in the serum levels of phosphodiesterase enzyme activity in asthma patients (mean = 14.939 ± 3.021 ng/mL) compared with a control group (mean = 9.974 ± 2.032 ng/mL). The result also showed a highly significant (p < 0.01) decrease in the serum levels of phosphodiesterase activity in patients of asthma disease with theophylline (mean = 11.253 ± 2.479 ng/mL) compared to serum patients without nano and control groups. It is vital that the result showed a highly significant (p < 0.01) decrease in the serum levels of phosphodiesterase activity in patients of asthma disease with copper nano complex (mean = 9.563 ± 2.082 ng/mL) compared in patients of asthma disease with and without theophylline. As for comparing asthma disease with copper nano complex and control group, the result showed there was no significant effect (p > 0.05).